Information design with teaching and learning in mind. Issue 4 (1st October 2016) - Pettersson, Rune; Avgerinou, Maria D.
Abstract: Based on the existing research from Cognitive Psychology, Information Design, Instructional Design, and Multimedia Design, it is possible to develop recommendations for the design of learning experiences that facilitate, support and enrich student academic performance. This article concentrates on the role of the teacher as information designer in print, and in digital environments within a twenty-first century education framework. We also propose specific guidelines that are based on information, and multimedia research design, with the view of assisting the teacher-designer combine content, modalities and media, and design information and instruction sets that are effective and appropriate for the intended receivers, thus optimizing their potential for learning.